Association between metabolic score for insulin resistance and stroke: a nationally representative cross-sectional study from NHANES 2007–2018 - Lingtian Weng; Yuqiu Lu; Hanning Song; Jiayi Xu; Xuhong Jiang; Xuhong Jiang (Frontiers in Neurology)
BackgroundStroke is a significant cerebrovascular disease and remains one of the leading causes of death and disability worldwide. Insulin resistance has been strongly linked to the incidence of stroke. Employing characteristics of metabolic syndrome, the Metabolic Score for Insulin Resistance (METS-IR) accurately measures insulin resistance. Nonetheless, the relationship between METS-IR and stroke risk is not well-established.MethodsWe analyzed data from the National Health and Nutrition Examination Survey (NHANES) covering the years 2007–2018. Participants providing complete METS-IR data and self-reported stroke information were included in the study. We utilized weighted multivariate regression to explore the relationship between METS-IR and stroke, performing subgroup analyses as well.ResultsA total of 14,794 participants were included, with an average METS-IR of 43.44 ± 12.68. The overall prevalence of self-reported stroke was 3.79%, with higher rates observed in upper METS-IR tertiles. An increase of one unit in METS-IR was associated with a 1% increase in stroke risk (OR = 1.01; 95% CI: 1.01–1.02). Interaction tests indicated no significant effects of gender, smoking status, alcohol consumption, hypertension, diabetes, physical activity, or serum cholesterol levels on this relationship. Notably, for participants younger than 60 years, the association was significantly stronger (OR = 1.02; 95% CI: 1.01–1.03), with a marked interaction (p = 0.0061).ConclusionOur findings indicate a positive correlation between higher METS-IR and increased stroke risk. Early intervention targeting insulin resistance may be a viable preventive measure against stroke, particularly in individuals under 60 years of age.